2000
DOI: 10.1093/bja/85.6.841
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurement of needle insertion depth in paravertebral blocks in women

Abstract: Single-injection paravertebral block offers adequate unilateral analgesia for thoracic and upper abdominal surgery. This technique is easy to learn but there is a risk, albeit low, of pleural puncture. The aim of the study was to determine whether sonographic measurements of the distances from the skin to the transverse process and to the parietal pleura are useful for calculating the required depth of needle insertion. Before puncture of the paravertebral space, the distances from the skin to the transverse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 4 publications
3
34
1
4
Order By: Relevance
“…First, we could infiltrate the PV area easily, but similar to the description of Luyet et al [8], the catheter placement was difficult in only one patient (Patient 2), in which we needed to readjust the Tuohy needle. Otherwise, the respective depths of location were comparable to those already reported [8,9], which is especially relevant for the series of Pusch et al [9], whose patients were all female as in our series, while Riain et al [6] reported having taken the same amount of time to perform PV blocks (between 8 and 10 minutes). The main difference is the duration of the preliminary localization needed under our specific conditions because of the deep local changes resulting from the laminectomy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, we could infiltrate the PV area easily, but similar to the description of Luyet et al [8], the catheter placement was difficult in only one patient (Patient 2), in which we needed to readjust the Tuohy needle. Otherwise, the respective depths of location were comparable to those already reported [8,9], which is especially relevant for the series of Pusch et al [9], whose patients were all female as in our series, while Riain et al [6] reported having taken the same amount of time to perform PV blocks (between 8 and 10 minutes). The main difference is the duration of the preliminary localization needed under our specific conditions because of the deep local changes resulting from the laminectomy.…”
Section: Discussionsupporting
confidence: 90%
“…Until now, the published data [6][7][8][9][10][11][12] on USG catheterization has involved only patients with normal anatomy. Among the interesting recently published data [6][7][8]11,12] are two methods to approach the PV area.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve stimulator guidance to improve the needle-nerve position or ultrasound guidance increases the accuracy and efficacy of TPVB, thus minimizes the incidence of side effects or complications [2,9,12,14,15]. Ultrasonography is useful to guide the needle tip into the thoracic paravertebral space,visualize the catheter and drug spread allowing lesser volume of LA that minimize the risk of complications like accidental intravascular injection, pleural puncture or pneumothorax and thus improves the therapeutic success [24][25][26]. Although less practiced USG guidance is currently recommended but availability of ultrasound, adequate training and development of skill is required.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,10 Additional postoperative benefits include a reduction in opioid requirements, earlier hospital discharge, 11 and a possible decreased risk for metastases and recurrence following surgery for breast cancer. 12 Several techniques have been described for entering the paravertebral space, including loss of resistance, nerve stimulator-guided, lateral/ intercostal approach, ultrasound assisted, 13 and even x-ray 8 and CT scan verified approaches. 14 Although the overall incidence of complications of paravertebral blocks is very low, 15,16 the risk of pneumothorax and unintended intrathecal injections remain an important clinical concern.…”
Section: Résultats : à L'exception De T5 Une Relation Linéaire a Pu mentioning
confidence: 99%